Cooling performance of a Li-ion cylindrical battery pack with liquid circulating pipes embedded in phase change material - Jilte, Ravindra; Afzal, Asif; Khan, Sher Afghan; Asif, Mohammad; Venkatesan, Elumalai Perumal; Munimathan, Arunkumar (Elsevier Ltd Kidlington Corporate Office, Kidlington, United Kingdom, 2024)
In global efforts to reduce carbon emissions from conventional IC-engine-powered vehicles, several countries have taken steps to adopt electric vehicles (EVs) as alternate transport options. Lithium-ion batteries are widely used as power sources and a battery thermal management system (BTMS) is needed to ensure that the battery operates within the optimal operating temperature. In this study, the battery module is designed to have a single inlet and outlet as well as provisions for supplying and removing coolants on the same side. This facilitates easier placement of systems considering the constraints of electric vehicles. The hybrid cooling system is proposed utilizing the effectiveness of the phase change material in addition to the active mode of liquid cooling for twenty-five 18650 Li-ion batteries arranged in 5S5P pack configuration with a resultant target capacity of 12500 mAh and 18 V. The hybrid battery cooling systems are designed in three configurations based on the number of water-circulating pipes embedded in a phase change material (PCM) container: 4V3H, 6V5H, and 8V7H where V and H represent vertical and horizontal pipes. Detailed procedures have been included for the structural design and realization of the hybrid cooling system. With the proposed hybrid cooling systems, the maximum battery pack temperature could be restricted below 43 ◦C when the battery packs were subjected to 4C discharge conditions at an ambient temperature of 35 ◦C for a 4C3H system. The maximum temperature non-uniformity was found less than 0.86 ◦C. A battery pack operating at a higher ambient temperature of 40 ◦C, the effective use of PCM and water circulating tubes keeps the maximum battery temperature below 45 ◦C and maximum temperature non-uniformity below 0.75 ◦C.